GESTION DE LA INNOVACIÓN: UN RETO EN LA EBC (Economía y Sociedad, 2007)
ResumenEste artículo presenta los resultados más relevantes de un estudio de percepción sobre la gestión de la innovación en las  organizaciones en Costa Rica en los que participó el autor; sus  orígenes, efectos y obstáculos, las prácticas y experiencias en  innovación, la participación, éxito y fracaso en la gestión de la innovación, las características de los egresados universitarios  para favorecer los procesos de innovación, y los retos en materia de gestión de la innovación que tiene la universidad en una economía basada en el conocimiento. Como orientación  conceptual y metodológica se utilizó el Manual de Oslo: Proposed Guidelines for Collecting and Interpreting Technological Innovation, propuesto por la Organización para el Desarrollo y la Cooperación Económica.AbstractThis article presents the most excellent results of a perception study on the management of the innovation in the organizations in Costa Rica in which the author participated; its origins, effects and obstacles, the practices and experiences in innovation, the participation, success and failure in the management of the  innovation, the characteristics of the university withdrawn ones to favor the processes of innovation, and the challenges in the matter of management of the innovation that has the university in an economy based on the knowledge. As conceptual and methodologic direction were used the Manual of Oslo: Proposed for Guidelines Collecting and Interpreting Technological Innovation, proposed by the Organization for the Development and the Economic Cooperation.